Occupational Health And Safety Among Seafarers Through The Lens Of Job Demands-Resources Theory: A Systematic Literature Review From A Human Resource Management Perspective - Andi Nurfiana Haz; Muh Nurfadel Hamzah (Institute of Advanced Knowledge and Science, 2026)
Seafarers sustain global maritime logistics, yet they work in isolated, mobile, and safety-critical environments where fatigue, long working hours, psychosocial stress, limited access to medical support, and exposure to physical hazards remain persistent occupational risks. This systematic literature review synthesizes recent evidence on occupational health and safety (OHS) among seafarers through the Job Demands-Resources (JD-R) Theory from a Human Resource Management (HRM) perspective. Following PRISMA 2020 principles, the review mapped peer-reviewed studies, official reports, and selected credible sources published primarily between 2020 and 2026, while retaining seminal JD-R and maritime safety studies for theoretical grounding. The synthesis indicates that seafarers' OHS problems are not merely technical or regulatory issues; they are strategic HRM challenges shaped by the interaction between job demands and job resources. High workload, fatigue, isolation, sleep disruption, emotional demands, time pressure, and environmental hazards increase burnout, psychological strain, unsafe behavior, and accident risk. Conversely, safety leadership, organizational support, safety training, welfare facilities, autonomy, social support, communication, and safety climate function as protective resources that reduce strain and enhance engagement, safety behavior, and retention intention. The review contributes by integrating maritime OHS, employee well-being, and safety performance within a JD-R framework. It offers a conceptual model for future empirical testing using SEM, PLS-SEM, or AMOS and provides practical recommendations for shipping companies, HR managers, ship leaders, regulators, and maritime training institutions.